Health and well-being of serving and ex-serving UK Armed Forces personnel: protocol for the fourth phase of a longitudinal cohort study - Howard Burdett; Neil Greenberg; Sharon Stevelink; Margaret Jones; Lisa Hull; Deirdre MacManus; Dominic Murphy; Nicola T Fear; Simon Wessely; Daniel Leightley; Marie-Louise Sharp; Amos Simms; et al. (BMJ Open, 2023)
Introduction This is the fourth phase of a longitudinal cohort study (2022–2023) to investigate the health and well-being of UK serving (Regulars and Reservists) and ex-serving personnel (veterans) who served during the era of the Iraq and Afghanistan conflicts. The cohort was established in 2003 and has collected data over three previous phases including Phase 1 (2004–2006), Phase 2 (2007–2009) and Phase 3 (2014–2016).Methods and analysis Participants are eligible to take part if they completed the King’s Centre for Military Health Research Health and Wellbeing Cohort Study at Phase 3 (2014–2016) and consented to be recontacted (N=7608). Participants will be recruited through email, post and text message to complete an online or paper questionnaire. Data are being collected between January 2022 and September 2023. Health and well-being measures include measures used in previous phases that assess common mental disorders, post-traumatic stress disorder (PTSD) and alcohol misuse. Other areas of interest assess employment, help-seeking and family relationships. New topics include the impact of the British withdrawal from Afghanistan in 2021, complex PTSD (C-PTSD), illicit drug use, gambling and loneliness. Analyses will describe the effect size between groups deployed to Iraq and/or Afghanistan or not deployed, and those who are currently in service versus ex-service personnel, respectively, reporting prevalences with 95% CIs, and ORs with 95% CI. Multivariable logistic and multiple linear regression analyses will be conducted to assess various health and well-being outcomes and associations with risk and protective factors.Ethics and dissemination Ethical approval has been granted by the Ministry of Defence Research Ethics Committee (Ref: 2061/MODREC/21). Participants are provided with information and agree to a series of consent statements before taking part. Findings will be disseminated to UK Armed Forces stakeholders and international research institutions through stakeholder meetings, project reports and scientific publications.